Multidimensional Factors Can Explain the Clinical Worsening in People With Parkinson's Disease During the COVID-19 Pandemic: A Multicenter Cross-Sectional Trial - Silva-Batista, Carla; Coelho, Daniel Boari; Júnior, Renato Campos Freire; Almeida, Lorena Rosa; Guimarães, Adriana; Nóbrega, Katia Cirilo Costa; Machado Sanchez, Hugo; Lindquist, Ana Raquel Rodrigues; Israel, Vera Lúcia; Kanegusuku, Hélcio; Guimarães, Rachel; Beckmann Bosaipo, Nayanne; et al. (Frontiers in Neurology, 2021)
Background: Self-reported clinical worsening by people with Parkinson’s disease (PD) during social distancing may be aggravated in Brazil, where e/tele-health system is precarious. Objectives: To investigate self-reported changes in motor and non-motor aspects during social distancing in people with PD living in Brazil. To investigate factors that might explain these changes. Methods: In this multicenter cross-sectional trial, 478 people with diagnosis of idiopathic PD (Mean age=67, SD=9.5; 167 female) were recruited from 14 centers distributed through the five geographical regions of Brazil. Evaluators from each center applied a questionnaire by telephone, which included questions (previous and current period of social distancing) about the motor and non-motor experiences of daily living, quality of life, daily routine, and physical activity volume. Results: Self-reported clinical worsening in non-motor and motor aspects of daily life experiences (Movement Disorder Society-Unified PD Rating Scale parts IB and II, emotional and mental health, and fear of falling) and in quality of life were observed. Only 31% of the participants reported home-based physical activity with distance-guided supervision. Perceived changes in quality of life, freezing of gait, decreased physical activity volume, daily routine, and fear of falling explained self-reported clinical worsening (P<0.05). Conclusions: Self-reported clinical worsening in people with PD living in Brazil during social distancing can also be aggravated by precarious e/tele-health system, as perception of decreased physical activity volume and impoverishment in daily routine were some of the explanatory factors. Considering the multifaceted worsening, the implementation of remote multi-professional support for these people is urgent.